2017
DOI: 10.15358/0344-1369-2017-4-37
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Differences in Segment-specific Willingness-to-pay for the Fair Trade Label

Abstract: The authors would like to thank two anonymous referees for their helpful and constructive comments as well as the co-editor of the special section, Udo Wagner, for his detailed feedback and suggestions. Furthermore, the authors benefitted from critical discussions with participants at the 5 th French-Austrian-German Workshop on Consumer Behavior. Daniel Guhl gratefully acknowledges support by the Deutsche Forschungsgemeinschaft (DFG) through CRC TRR 190.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Similar to green consumption, different types of variables, e.g., geographical, cultural, sociodemographic, and psychographic, are used to profile social consumers. Social consumers were frequently identified to be predominantly female [33][34][35], young [36,37], have a higher level of income [35], live in smaller households [23], and have a higher level of education [35,36,38]. In addition, cultural determinants for fair trade consumption have been maintained [39].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to green consumption, different types of variables, e.g., geographical, cultural, sociodemographic, and psychographic, are used to profile social consumers. Social consumers were frequently identified to be predominantly female [33][34][35], young [36,37], have a higher level of income [35], live in smaller households [23], and have a higher level of education [35,36,38]. In addition, cultural determinants for fair trade consumption have been maintained [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, several operational challenges concerning adequate prices for a (newly introduced) fair trade product (variant) and advertising campaigns have to be addressed by a company. In the field of fair trade product pricing, many research studies on consumers' willingness to pay for fair trade products have recently been published [34,47]. However, it must be considered that a willingness to pay does not translate into the acceptance of a high price premia for fair trade products per se.…”
Section: Inferences On Sustainable Brand Personalitiesmentioning
confidence: 99%
“…Numerous studies dedicated to the socio-demographic backgrounds of ethical consumers included consumers having an interest and buying fair trade products. The body of literature is, however, not conclusive [4,[59][60][61]. While older studies have identified people with higher education, higher income, and being female as relevant socio-demographic factors impacting ethical food purchasing behaviour [47], more recent studies have found that socio-demographic factors are not good predictors of ethical food purchasing behaviour [8,34,53,54].…”
Section: Socio-demographic Informationmentioning
confidence: 99%
“…However, even if the influence of (socio-) demographic variables is supported, the direction of the influence is contradictory across different studies. While some researchers have described sensitive consumers as female (e.g., Paetz and Guhl 2017) or young (e.g., De Pelsmacker et al 2005), other studies found older (Carrigan et al 2004) consumers to be more sensitive to social product attributes. At first glance, those ambivalences may be traced back to several determinants, e.g., varying focal product categories, varying cultural contexts, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed explanation of the calculation of a consumer's willingness-to-pay of the FT label from preference parameters, please refer toPaetz and Guhl (2017).…”
mentioning
confidence: 99%